2011
DOI: 10.3788/col201109.040601
|View full text |Cite
|
Sign up to set email alerts
|

用于1.55 μm波段超连续谱产生的高非线性色散平坦光子晶体光纤

Abstract: Long Zheng ( ), Xia Zhang ( ) * , Xiaomin Ren ( ), Huifang Ma ( ), Lei Shi ( ), Yamiao Wang ( ), and Yongqing Huang ( )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The supercontinuum generation (SCG) in photonic crystal fiber (PCF) is an intensively research topic in optical and photonic science in the last decade [1][2][3][4]. Along with the research of SCG, the corresponding SC sources have already found their applications in optical coherence tomography (OCT), pump-probe spectroscopy, metrology or non-linear microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The supercontinuum generation (SCG) in photonic crystal fiber (PCF) is an intensively research topic in optical and photonic science in the last decade [1][2][3][4]. Along with the research of SCG, the corresponding SC sources have already found their applications in optical coherence tomography (OCT), pump-probe spectroscopy, metrology or non-linear microscopy.…”
Section: Introductionmentioning
confidence: 99%